Mengulas Dan Memahami Kinerja Guru - Nehemia Nome (STT Pelita Dunia, 2018)
Abstract: This study discusses how to understand teacher performance in a simple yet scientific review. Using a qualitative approach, the researcher found that the teacher's performance in this study was a success achieved by the teacher in teaching activities or the teaching and learning process. The teacher's performance can be seen from the skills in making teaching plans. Teaching skills and the ability to build interpersonal relationships. Abstrak: Penelitian ini membahas tentang bagaimana memahami kinerja guru dalam sebuah ulasan sederhana namuan ilmiah. Menggunakan pendekatan kualitatif, peneliti menemukan bahwa kinerja guru dalam penelitian ini adalah suatu keberhasilan yang dicapai guru dalam aktivitas mengajar atau proses belajar mengajar. Kinerja guru ini terlihat dari keterampilan membuat rencana pengajaran. Keterampilan mengajar dan kemampuan membina hubungan antar pribadi.